Preparation method of graphite-based boride ceramic modified Si-SiC ceramic coating material

By preparing graphite-based medium-entropy (Ti1/3Zr1/3Ta1/3)B2 boride ceramic modified Si-SiC coating, the problem of poor oxidation resistance of Si-SiC coating at high temperature was solved, and the high-temperature stability and oxidation resistance of the coating were improved.

CN120664905AActive Publication Date: 2025-09-19ZHENGZHOU UNIV

Patent Information

Application Number
CN202510860782.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-09-19
Estimated Expiration
2045-06-25

AI Technical Summary

Technical Problem

Existing Si-SiC coatings have poor oxidation resistance at high temperatures and are prone to oxidation failure. In addition, SiC coatings are brittle and easily crack or peel off under external loads.

Method used

Graphite-based medium-entropy (Ti1/3Zr1/3Ta1/3)B2 boride ceramic powder is mixed with Si and SiC, and a graphite-based (Ti1/3Zr1/3Ta1/3)B2-Si-SiC ceramic coating material is prepared by spark plasma sintering to form a single-phase solid solution, thereby improving the density and bonding strength of the coating.

Benefits of technology

The high-temperature oxidation resistance and density of the Si-SiC coating are significantly improved, a protective oxide layer is formed, and the high-temperature stability and oxidation resistance of the coating are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120664905A_ABST
    Figure CN120664905A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of graphite-based ceramic coating materials, in particular to a preparation method of a graphite-based boride ceramic modified Si-SiC ceramic coating material. Metal oxide powder of TiO2, ZrO and Ta2O5, B4C and C powder are subjected to ball milling and mixing and then subjected to two times of vacuum heat treatment to obtain single-phase medium-entropy boride ceramic, then the single-phase medium-entropy boride ceramic serves as a modifier to be mixed with Si and SiC and then subjected to spark plasma sintering, and the graphite-based (Ti1 / 3Zr1 / 3Ta1 / 3) B2-Si-SiC ceramic coating material is obtained. The medium-entropy boride ceramic with excellent high-temperature oxidation resistance is prepared by adopting a boron / carbon thermal reduction method and a discharge plasma sintering method, the molecular formula of the medium-entropy boride ceramic is (Ti1 / 3Zr1 / 3Ta1 / 3) B2, the medium-entropy boride ceramic has a close-packed hexagonal structure, and when the medium-entropy boride ceramic is used for doping modification of a Si-SiC coating, the density and the high-temperature oxidation resistance of the Si-SiC coating can be remarkably improved, and the high-temperature oxidation resistance of the Si-SiC coating can be remarkably improved. Wide application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite-based ceramic coating materials, and in particular to a method for preparing a graphite-based boride ceramic-modified Si-SiC ceramic coating material. Background Art

[0002] Traditional ultrahigh-temperature ceramics, including borides such as ZrB2, HfB2, and TaB2, have high melting points, excellent oxidation resistance, and mechanical properties, making them widely used in aerospace, energy, and extreme manufacturing. However, in extreme environments, due to the inherent brittleness of traditional ultrahigh-temperature ceramics, their mechanical properties and stability need to be improved.

[0003] Among ceramic materials, medium / high entropy ceramics significantly improve the comprehensive properties of materials through mechanisms such as lattice distortion, hysteresis diffusion, cocktail effect and enhanced thermodynamic stability. Therefore, medium / high entropy ceramics, as emerging members of the multi-element ultrahigh temperature ceramic family, have attracted the interest of researchers. In 2016, Gild et al. first prepared (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )B2 and other 7 high entropy boride ceramics, the hardness and oxidation resistance of these ceramics are generally better than those of single-component diborides made by the same manufacturing process. Ni et al. studied high entropy carbide ceramics (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )C was subjected to ablation in an oxyacetylene flame at 2000℃, and it was found that the composite oxide produced during the ablation process provided an effective oxygen barrier capability.

[0004] At present, the research on multi-element solid solution ultra-high temperature ceramics mainly focuses on high entropy ceramics, whose good performance is due to their unique entropy effect and multi-element synergistic effect. However, due to the large differences in the physical and chemical properties of multiple elements involved and different elements, it is difficult to explain the mechanism of high entropy ceramics having good performance. For this reason, some researchers choose medium entropy ceramics with fewer elements. In order to explore the influence of the types of components in multi-element ultra-high temperature ceramics on their performance, Zhang et al. studied C / C composites (Hf 1 / 3 Zr 1 / 3 Ta 1 / 3)C solid solution ceramic coating ablation performance at 2100 ℃, the dense oxide film formed during the ablation process makes the material have a low linear ablation rate (-0.61μm / s). Huo et al. prepared medium-entropy (Ta,Zr,Ti)B2 ceramics with 10vol.% metallic cobalt and 20vol.% SiC as additives, and studied its friction performance under different loads. The oxide layer formed during the friction process effectively reduced the friction coefficient under a high load of 10N (0.459). However, the materials prepared by the above research are not single-phase solid solution medium-entropy ceramics, and there is currently little research on single-phase medium-entropy ceramics.

[0005] Carbon materials (graphite and carbon / carbon composites) are among the most promising materials for aerospace hot-end components. However, they are susceptible to oxidation above 450°C. SiC-based ceramic coatings exhibit excellent thermochemical and thermophysical compatibility with carbon materials, forming a protective silicate glassy oxide layer containing SiO₂, which effectively improves the material's oxidation resistance. However, SiC coatings are inherently brittle and easily crack or peel off from the carbon substrate under high external loads. Furthermore, the SiO₂ produced by oxidation readily evaporates at high temperatures, creating a large number of pores and bubbles in the SiO₂ oxide film, ultimately leading to the failure of the SiC-based composite coating. Currently, medium- and high-entropy ceramics have become candidates for novel ultrahigh-temperature protective coatings. The wide melting point range of complex oxides formed at high temperatures by medium- and high-entropy ceramics, coupled with the introduction of entropy effects, make them suitable as essential components of ultrahigh-temperature protective coatings, improving the oxidation resistance of carbon materials. At present, there is little research and application on medium / high entropy ceramic coatings or medium / high entropy ceramic modified traditional coatings. Introducing medium-entropy ceramics into Si-SiC coatings is expected to develop a new type of ultra-high temperature protective coating for use in extreme environments such as aerospace. Summary of the Invention

[0006] The purpose of the present invention is to provide a method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material to solve the problem of poor high-temperature oxidation resistance of existing Si-SiC coatings.

[0007] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material, comprising the following steps:

[0008] S1. Preparation of boride ceramic powder

[0009] Take TiO2, ZrO2, Ta2O5, B4C and C raw material powder, mix them thoroughly and then heat treat them to obtain boride ceramic powder. The boride ceramic powder is medium entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3) B2 ceramic powder, a single-phase solid solution with a close-packed hexagonal structure;

[0010] S2. Preparation of boride ceramic powder, Si and SiC mixed powder and pretreatment of graphite matrix

[0011] The boride ceramic powder obtained in S1, Si and SiC raw material powders are mixed thoroughly to obtain a mixed powder; a graphite substrate is ground and polished, ultrasonically cleaned, and dried to obtain a pretreated graphite substrate;

[0012] S3, graphite-based (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) Preparation of B2-Si-SiC ceramic coating materials

[0013] The mixed powder obtained by S2 is coated on the pre-treated graphite substrate and subjected to spark plasma sintering to obtain the graphite-based (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2-Si-SiC ceramic coating material.

[0014] Furthermore, in the S1, the particle size of each raw material powder is 1 to 3 μm, and the purity is ≥99.9%; the molar ratios of TiO2, ZrO2, Ta2O5, B4C and C are 1:1:0.5:1.65-3:3-8 respectively; wherein the molar amount of B4C exceeds the molar amount of B4C required according to the stoichiometric ratio by at least 10%.

[0015] Furthermore, in the above S1, the raw material powders are fully mixed by ball milling, dried and sieved after ball milling to obtain the corresponding mixed powder, the obtained mixed powder is pressed into blocks and then heat-treated in a vacuum sintering furnace to obtain ceramic blocks, the obtained ceramic blocks are crushed and sieved and then heat-treated in a vacuum sintering furnace to obtain single-phase (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 ceramic powder.

[0016] Furthermore, in the primary heat treatment and the secondary heat treatment, the vacuum degree is less than 5 Pa; the temperature of the primary heat treatment is not less than 1450° C., and the temperature of the secondary heat treatment is not less than 2000° C.;

[0017] Furthermore, in the primary heat treatment and the secondary heat treatment, the heating rate is 10°C / min below 1000°C; 8°C / min between 1000 and 1500°C; 5°C / min above 1500°C; the holding time is not less than 1h; after the heat treatment, the temperature is reduced to 1000°C at a rate of 10°C / min and naturally cooled to room temperature in the furnace.

[0018] Furthermore, in the S2, the mass ratios of the medium-entropy boride ceramic powder, Si and SiC raw material powders are 5:4:16 respectively, wherein the particle size of the Si and SiC raw material powders is ≤200 mesh; the raw material powders are fully mixed by ball milling, dried and sieved after ball milling to obtain the corresponding mixed powder.

[0019] Furthermore, in the S2, the graphite substrate is a graphite disc with a size of Φ18mm×3mm; the graphite disc is pretreated by primary grinding and polishing, water washing, secondary grinding and polishing, water washing, ultrasonic cleaning, and drying; 200 mesh SiC sandpaper is used for the primary grinding and polishing, and 800 mesh SiC sandpaper is used for the secondary grinding and polishing.

[0020] Furthermore, in the above-mentioned S3, during the spark plasma sintering, the vacuum degree is less than 5 Pa, the sintering temperature is not less than 1900° C., and the sintering pressure is 40 MPa.

[0021] Furthermore, during the spark plasma sintering, the heating rate is 100°C / min below 1000°C; 50°C / min between 1000 and 1500°C; and 30°C / min above 1500°C. The holding time is not less than 10 minutes. After sintering is completed, the temperature is lowered to 1000°C at a rate of 50°C / min and then cooled to room temperature with the furnace.

[0022] Beneficial effects of the present invention:

[0023] In the present invention, entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 boride ceramics are single-phase solid solutions with a close-packed hexagonal structure, high purity and dense structure. (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )The preparation method of B2-Si-Si ceramic coating is simple to operate, the coating is tightly bonded to the substrate, the coating surface is smooth, the components are evenly distributed, and the thickness is controllable; the present invention effectively improves the high-temperature oxidation resistance of the Si-SiC coating by introducing medium-entropy boride ceramics, provides a new way to modify the Si-SiC coating, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is Example 1 of the present invention (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) X-ray diffraction pattern of B2 boride ceramic powder;

[0025] Figure 2 This is Example 1 of the present invention (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3) X-ray diffraction pattern of B2-Si-SiC coating;

[0026] Figure 3 This is Example 1 of the present invention (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) Surface morphology of B2-Si-SiC coating;

[0027] Figure 4 This is Example 1 of the present invention (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) Cross-sectional morphology of B2-Si-SiC coating;

[0028] Figure 5 This is Example 1 of the present invention (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) Oxidation curve of B2-Si-SiC coating oxidized at 1500℃ for 40h;

[0029] Figure 6 This is Example 1 of the present invention (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) Surface morphology of the B2-Si-SiC coating after oxidation at 1500℃ for 40h;

[0030] Figure 7 is the X-ray diffraction pattern of the ceramic powder obtained in Comparative Example 1 of the present invention;

[0031] Figure 8 This is an oxidation curve of the Si-SiC coating obtained in Comparative Example 2 of the present invention oxidized at 1500°C for 10 hours. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be described clearly and completely below with reference to the accompanying drawings in the embodiments of the present invention.

[0033] Example 1

[0034] The raw material powders of TiO2, ZrO2, Ta2O5, BC, and C were calculated and weighed in a molar ratio of 1:1:0.5:1.65:5, wherein the molar amount of BC exceeded the stoichiometric molar amount by 10%. The particle size of each of the raw materials was 1-3 μm and the purity was ≥99.9%. Subsequently, the raw material powders, 3 mm diameter zirconia balls, and anhydrous ethanol were added to a ball mill at a mass ratio of 1:5:5. The roller milling time and speed were 90 rpm for 12 hours. After ball milling, the grinding balls were separated from the slurry using a 30-mesh stainless steel sieve. The separated slurry was dried in a constant temperature drying oven at 80°C for 12 hours. The dried powder was sieved using a 200-mesh stainless steel sieve to obtain a uniformly mixed raw material powder.

[0035] The mixed powder is pressed into a block, placed in a graphite crucible, and subjected to boron / carbon thermal reduction reaction in a vacuum sintering furnace. The vacuum degree in the furnace is less than 5 Pa, and the temperature is raised to 1450°C for heat treatment. Below 1000°C, the heating rate is 10°C / min; from 1000 to 1450°C, the heating rate is 8°C / min; after heating, the temperature is kept warm for 2 hours, and then the temperature is lowered to 1000°C at a rate of 10°C / min, and finally cooled to room temperature with the furnace to obtain a ceramic block.

[0036] The obtained ceramic block was crushed and ground in an agate mortar and passed through a 200-mesh sieve to obtain ceramic powder; the obtained ceramic powder was pressed into a block, placed in a graphite crucible, and subjected to secondary heat treatment at 2000°C in a vacuum sintering furnace, with a heating rate of 10°C / min below 1000°C; a heating rate of 8°C / min between 1000 and 1500°C; and a heating rate of 5°C / min above 1500°C; after heating, the temperature was kept for 2 hours, and then the temperature was reduced to 1000°C at a rate of 10°C / min, and finally cooled to room temperature with the furnace, and the obtained ceramic block was crushed and ground in an agate mortar and passed through a 200-mesh sieve to obtain a single-phase (TiO2) 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 ceramic powder (TZTB), measured its X-ray diffraction pattern, and compared it with the X-ray diffraction pattern calculated by the software Materials Studio. The results are as follows Figure 1 As shown. Figure 1 It can be concluded that the diffraction peak intensity and position of the experimental results are consistent with the calculated results, and no other impurity phases are detected, indicating that a single-phase medium-entropy boride ceramic with a close-packed hexagonal crystal structure has been successfully synthesized.

[0037] Boride ceramic powder, Si powder and SiC powder were weighed in a mass ratio of 5:4:16, wherein the particle size of Si powder and SiC powder was ≤200 mesh. Subsequently, the raw material powders, zirconia balls with a diameter of 3 mm and anhydrous ethanol were added to a ball mill in a mass ratio of 1:5:5. The roller milling time and speed were 12 h and 90 rpm, respectively. After ball milling, the grinding balls in the slurry were separated using a 30-mesh stainless steel sieve, and the separated slurry was placed in a constant temperature drying oven at 80°C and dried for 12 h. The dried powder was sieved using a 200-mesh stainless steel sieve to obtain a mixed powder of boride ceramic powder, Si and SiC.

[0038] The graphite substrate was pretreated; a Φ18mm×3mm graphite disc was used as the substrate; first, the graphite disc was manually polished on 200-mesh SiC sandpaper for 2 minutes, and the residual particles on the graphite surface were washed away with clean water. Then, 800-mesh SiC sandpaper was used for polishing for 2 minutes to wash away the residual particles on the surface. After that, the disc was ultrasonically cleaned at a frequency of 40kHz for 5 minutes to remove impurities and then placed in a constant temperature drying oven at 80°C for 12 hours.

[0039] The mixed powder and the pretreated graphite matrix were then placed in a Φ20mm spark plasma sintering mold, with the powder and the mold separated by clean carbon paper; 1.5g of powder was weighed to wrap the graphite matrix in the center, and the surface of the powder was flattened after each step to ensure the uniformity of the coating; after the mold was installed, spark plasma sintering was used, with a sintering temperature of 1900°C, a holding time of 20min, and a sintering pressure of 40MPa.

[0040] The sintering temperature program is as follows: below 1000℃, the heating rate is 100℃ / min; 1000-1500℃, the heating rate is 50℃ / min; above 1500℃, the heating rate is 30℃ / min; during the cooling process, the temperature is cooled to 1000℃ at a rate of 50℃ / min, and then the program ends. The furnace is cooled to room temperature, and the carbon paper is removed by grinding and polishing with sandpaper to obtain the graphite-based (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2-Si-SiC ceramic coating material, its X-ray diffraction pattern is as follows Figure 2 Its surface and cross-sectional morphologies are shown as follows. Figure 3 、 Figure 4 As shown, the prepared coating material has a smooth surface, uniform composition distribution, and is tightly bonded to the substrate, wherein the white phase is medium-entropy boride ceramics and the black phase is Si-SiC.

[0041] The obtained (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3After B2-Si-SiC ceramic coating material was oxidized at 1500℃ for 40h, the mass per unit area increased by 6.81×10 -3 g / cm 2 , has good antioxidant properties, and its oxidation curve is as follows Figure 5 shown.

[0042] like Figure 6 As shown in the figure, after constant-temperature oxidation at 1500°C for 40 hours, an oxide layer forms on the coating. The black phase is SiO2, formed by the oxidation of Si and SiC. The light gray and dark gray phases represent solid solutions of SiO2 with the precipitated metal elements (Ti, Zr, and Ta), respectively. The white phases are metal oxides ZrO2 and TiTaO4. The SiO2 oxide layer protects the graphite matrix, and the metal oxides are pinned into the SiO2, enhancing the high-temperature stability of the oxide layer. Although the oxide layer contains a few cracks, it is generally relatively intact.

[0043] Through the medium entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 ceramic modified Si-SiC coating significantly improved the density, high temperature stability and high temperature oxidation resistance of Si-SiC coating.

[0044] Comparative Example 1

[0045] The raw material powders of TiO2, ZrO2, Ta2O5, BC, and C were weighed according to a stoichiometric ratio of 1:1:0.5:1.545:5, with a 3% molar excess of BC. Their particle sizes were all 1-3 μm, with a purity of ≥99.9%. Subsequently, the raw material powders, 3 mm diameter zirconia balls, and anhydrous ethanol were added to a ball mill at a mass ratio of 1:5:5. The milling time and speed were 90 rpm, respectively. After ball milling, the grinding balls were separated from the slurry using a 30-mesh stainless steel sieve. The separated slurry was dried in an 80°C constant temperature drying oven for 12 hours. The dried powder was then sieved using a 200-mesh stainless steel sieve to obtain a uniformly mixed raw material powder.

[0046] The mixed powder was pressed into a block, placed in a graphite crucible, and subjected to boron / carbon thermal reduction reaction in a vacuum sintering furnace. The vacuum degree in the furnace was less than 5 Pa, and the temperature was raised to 1450°C for heat treatment. After keeping the temperature for 2 hours, the temperature was lowered to 1000°C at a rate of 10°C / min, and finally cooled to room temperature with the furnace.

[0047] The ceramic block was crushed and ground in an agate mortar, sieved using a 200-mesh sieve, and the obtained ceramic powder was pressed into a block, placed in a graphite crucible, and subjected to a secondary heat treatment at 2000°C in a vacuum sintering furnace to finally obtain ceramic powder; wherein the heat treatment process was the same as in Example 1.

[0048] like Figure 7 As shown in the figure, the prepared ceramic powder exhibits diffraction peaks of TaC and TaB2, indicating that the powder is a mixture of these two substances. This shows that during the sintering process, the B4C content is relatively small and a medium-entropy boride ceramic with a single-phase solid solution cannot be formed.

[0049] Comparative Example 2

[0050] The raw material powders, Si and SiC, were weighed in a mass ratio of 1:4. Their particle sizes were 1-3 μm, with a purity of ≥99.9% and a particle size of ≤200 mesh. The raw material powders, 3 mm diameter zirconia balls, and anhydrous ethanol were then added to a ball mill in a mass ratio of 1:5:5. The milling time was 12 hours and the speed was 90 rpm, respectively. After ball milling, the grinding balls were separated from the slurry using a 30-mesh stainless steel screen. The separated slurry was dried in an 80°C constant temperature drying oven for 12 hours. The dried powder was then sieved using a 200-mesh stainless steel screen to obtain a uniformly mixed raw material powder.

[0051] The mixed powder is coated on a pretreated graphite substrate (graphite substrate pretreatment is the same as in Example 1), and is sintered at a high temperature of 1900° C. using a spark plasma sintering method (sintering procedure is the same as in Example 1) to obtain a graphite-based Si-SiC ceramic coating material.

[0052] After the Si-SiC ceramic coating material was oxidized at 1500℃ for 10h, the mass per unit area decreased by 6.05×10 -2 g / cm 2 , the antioxidant performance is poor, and its oxidation curve is as follows Figure 8 shown.

[0053] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, any technical solution that is the same or similar to that of the present application falls within the scope of protection of the present invention.

Claims

1. A method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material, characterized in that: The following steps are involved: S1. Preparation of boride ceramic powder Take TiO2, ZrO2, Ta2O5, B4C and C raw material powder, mix them thoroughly and then heat treat them to obtain boride ceramic powder. The boride ceramic powder is medium entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) B2 ceramic powder, a single-phase solid solution with a close-packed hexagonal structure; S2. Preparation of boride ceramic powder, Si and SiC mixed powder and pretreatment of graphite matrix The boride ceramic powder obtained in S1, Si and SiC raw material powders are mixed thoroughly to obtain a mixed powder; a graphite substrate is ground and polished, ultrasonically cleaned, and dried to obtain a pretreated graphite substrate; S3, graphite-based (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 ) Preparation of B2-Si-SiC ceramic coating materials The mixed powder obtained by S2 is coated on the pre-treated graphite substrate and subjected to spark plasma sintering to obtain the graphite-based (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2-Si-SiC ceramic coating material.

2. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 1, characterized in that: In the above-mentioned S1, the particle size of each raw material powder is 1-3 μm, and the purity is ≥99.9%; the molar ratios of TiO2, ZrO2, Ta2O5, B4C and C are 1:1:0.5:1.65-3:3-8 respectively; wherein the molar amount of B4C exceeds the molar amount of B4C required according to the stoichiometric ratio by at least 10%.

3. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 1, characterized in that: In the above S1, the raw material powders are fully mixed by ball milling, dried and sieved after ball milling to obtain the corresponding mixed powders, the mixed powders are pressed into blocks and then heat-treated in a vacuum sintering furnace to obtain ceramic blocks, the ceramic blocks are crushed and sieved and then heat-treated in a vacuum sintering furnace to obtain single-phase (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B2 ceramic powder.

4. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 3, characterized in that: In the primary heat treatment and the secondary heat treatment, the vacuum degree is less than 5 Pa; the temperature of the primary heat treatment is not lower than 1450°C, and the temperature of the secondary heat treatment is not lower than 2000°C.

5. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 4, characterized in that: In the primary heat treatment and the secondary heat treatment, the heating rate is 10°C / min below 1000°C; 8°C / min between 1000 and 1500°C; 5°C / min above 1500°C; the holding time is not less than 1 hour; after the heat treatment, the temperature is reduced to 1000°C at a rate of 10°C / min and naturally cooled to room temperature in the furnace.

6. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 1, characterized in that: In the S2, the mass ratio of the medium-entropy boride ceramic powder, Si and SiC raw material powders is 5:4:16, wherein the particle size of the Si and SiC raw material powders is ≤200 mesh; the raw material powders are fully mixed by ball milling, dried and sieved after ball milling to obtain the corresponding mixed powder.

7. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 1, characterized in that: In the S2, the graphite substrate is a graphite disc with a size of Φ18mm×3mm; the graphite disc is pretreated by primary grinding and polishing, water washing, secondary grinding and polishing, water washing, ultrasonic cleaning, and drying; the primary grinding and polishing uses 200 mesh SiC sandpaper, and the secondary grinding and polishing uses 800 mesh SiC sandpaper.

8. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 1, characterized in that: In the above-mentioned S3, during the spark plasma sintering, the vacuum degree is less than 5 Pa, the sintering temperature is not less than 1900° C., and the sintering pressure is 40 MPa.

9. The method for preparing a graphite-based boride ceramic modified Si-SiC ceramic coating material according to claim 8, characterized in that: During the spark plasma sintering, the heating rate is 100°C / min below 1000°C; 50°C / min between 1000 and 1500°C; and 30°C / min above 1500°C. The holding time is not less than 10 minutes. After sintering is completed, the temperature is lowered to 1000°C at a rate of 50°C / min and then cooled to room temperature along with the furnace.

Citation Information

Patent Citations

  • High-entropy boride ceramic material and preparation method thereof

    CN110606749A

  • Preparation method of medium-entropy boron carbide ceramic

    CN118637917A

  • Procede pour revetir une piece d'un revetement de protection contre l'oxydation

    FR2966455A1

  • Ablation-resistant high-entropy carbide-high-entropy diboride-silicon carbide multiphase ceramic and preparation thereof

    US20230167029A1

  • Process for coating a part with an oxidation-protective coating

    WO2012055865A1

Cited By

  • Preparation method of surface toughened silicon carbide coating of inorganic nonmetallic material

    CN122586609A